2018
DOI: 10.1128/jvi.00954-18
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Lassa Virus Entry Inhibitors from an FDA-Approved Drug Library

Abstract: Currently, there is no approved therapy to treat Lassa fever; therefore, repurposing of approved drugs will accelerate the development of a therapeutic stratagem. In this study, we screened an FDA-approved library of drugs and identified two compounds, lacidipine and phenothrin, which inhibited Lassa virus entry by blocking low-pH-induced membrane fusion. Additionally, both compounds extended their inhibition against the entry of Guanarito virus, and the viral targets were identified as the SSP-GP2 interface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 57 publications
4
86
0
2
Order By: Relevance
“…Instead, these data imply a direct interaction with the LASV glycoprotein. The unique SSP-GP2 interface of the arenavirus glycoprotein is crucial for viral fusion and is therefore an attractive target for antivirals, as many previously discovered arenavirus entry inhibitors, such as ST-193, F3406-2010, lassamycin-1 and lacidipine, all target this sensitive domain (Shankar et al, 2016;Thomas et al, 2011;Wang et al, 2018;York et al, 2008). Our fragment replacing mutational study of LASV-GP and LCMV-GP demonstrated that losmapimod also targets the LASV-SSP-GP2 interface.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Instead, these data imply a direct interaction with the LASV glycoprotein. The unique SSP-GP2 interface of the arenavirus glycoprotein is crucial for viral fusion and is therefore an attractive target for antivirals, as many previously discovered arenavirus entry inhibitors, such as ST-193, F3406-2010, lassamycin-1 and lacidipine, all target this sensitive domain (Shankar et al, 2016;Thomas et al, 2011;Wang et al, 2018;York et al, 2008). Our fragment replacing mutational study of LASV-GP and LCMV-GP demonstrated that losmapimod also targets the LASV-SSP-GP2 interface.…”
Section: Discussionmentioning
confidence: 70%
“…Not only does this suggest that the amino acid at position 435 plays a critical role in resistance to which is consistent with a previous report (Larson et al, 2008), but it also implies that the mode of function of losmapimod is different from that of and that the sequence variation within the SSP region does not affect losmapimod activity. Previous studies have demonstrated that mutations within the SSP or TM regions confer resistance to drugs such as lacidipine (Wang et al, 2018) and ST-193 (Larson et al, 2008), and it will be interesting to determine whether similar mutations arise in response to treatment with losmapimod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The packaging of recombinant VSV expressing JUNV GP was performed as described previously (Garbutt et al, 2004;Wang et al, 2018b). Briefly, the JUNV GPC gene was cloned into the plasmid pVSVΔG-eGFP (Addgene 31842) at the ΔG site to generate pVSVΔG-eGFP-JUNV GPC.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Results of screening drug libraries have revealed several other mammalian cell pathways that may be targeted. For example, blockers of Ca 2+ and other ion channels are reported to have in vitro activity against Ebola, Japanese Encephalitis virus, human cytomegalovirus and arenaviruses such as Lassa fever …”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%